Simultaneous purification of DNA and RNA from microbiota in a single colonic mucosal biopsy. (December 2016) - Moen, Aina; Tannæs, Tone; Vatn, Simen; Ricanek, Petr; Vatn, Morten; Jahnsen, Jørgen
Abstract Background Nucleic acid purification methods are of importance when performing microbiota studies and especially when analysing the intestinal microbiota as we here find a wide range of different microbes. Various considerations must be taken to lyse the microbial cell wall of each microbe. In the present article, we compare several tissue lysis steps and commercial purification kits, to achieve a joint RNA and DNA purification protocol for the purpose of investigating the microbiota and the microbiota-host interactions in a single colonic mucosal tissue sample. Results A further optimised tissue homogenisation and lysis protocol comprising mechanical bead beating, lysis buffer replacement and enzymatic treatment, in combination with the AllPrep DNA/RNA Mini Kit (Qiagen, Hilden, Germany) resulted in efficient and simultaneous purification of microbial and human RNA and DNA from a single mucosal colonic tissue sample. Conclusions The present work provides a unique possibility to study RNA and DNA from the same mucosal biopsy sample, making a direct comparison between metabolically active microbes and total microbial DNA. The protocol also offers an opportunity to investigate other members of a microbiota such as viruses, fungi and micro-eukaryotes, and moreover the possibility to extract data on microbiota and host interactions from one single mucosal biopsy.